2014
DOI: 10.1073/pnas.1316700111
|View full text |Cite
|
Sign up to set email alerts
|

Bcl2L13 is a ceramide synthase inhibitor in glioblastoma

Abstract: Significance Molecular mechanisms of therapy (apoptosis) resistance in cancer are poorly understood. Here, we have identified Bcl2-like 13 (Bcl2L13) as a ceramide synthase inhibitor that is overexpressed in glioblastoma (GBM) and other malignancies. Bcl2L13 inhibits therapy-induced apoptosis and promotes GBM tumor growth in vivo. Mechanistically, Bcl2L13 binds to proapoptotic ceramide synthases 2 (CerS2) and 6 (CerS6) and blocks CerS2/6 complex formation and activity. Correspondingly, CerS2/6 activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 30 publications
1
74
0
1
Order By: Relevance
“…Taken together, these results suggest that transcriptional activation of acid ceramidase in our model is not mediated by ceramide itself and does not depend on the catalytic activity of CerS. Recently it has been demonstrated that ectopically expressed Bcl2L13 binds to CerS6 (51). Therefore, one possibility is that elevated expression of acid ceramidase in response to CerS6 overexpression occurs as a consequence of altered protein-protein interactions with non-CerS proteins.…”
Section: Discussionsupporting
confidence: 59%
“…Taken together, these results suggest that transcriptional activation of acid ceramidase in our model is not mediated by ceramide itself and does not depend on the catalytic activity of CerS. Recently it has been demonstrated that ectopically expressed Bcl2L13 binds to CerS6 (51). Therefore, one possibility is that elevated expression of acid ceramidase in response to CerS6 overexpression occurs as a consequence of altered protein-protein interactions with non-CerS proteins.…”
Section: Discussionsupporting
confidence: 59%
“…1 ) has been used previously to assay CerS ( 17,18,21 ), no attempts have been made to minimize reaction volumes to allow the use of small amounts of biological material or to improve the mode of separating NBD-lipid substrates and products. We have now been able to decrease the reaction volume to a minimum of 20 µl, rather than the 100-250 µl used previously with [4, H]Sph ( 22 ) or with NBD-Sph ( 21 ), permitting the use of small amounts of protein for the assay.…”
Section: Optimizing Conditions For Use Of Nbd-sph In the Cers Assaymentioning
confidence: 99%
“…Because CerSs appear to be involved in the pathology of a number of human diseases (15)(16)(17)(18)(19), the assay that we have described in this study might prove useful in a clinical setting. Furthermore, SPE column chromatography could be were obtained using both methods with all three CerSs.…”
Section: Spe Chromatography To Separate Nbd Lipidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin has been reported to stimulate de novo ceramide synthesis by triggering dimerization and activation of ER-resident ceramide synthases (39,40) but also perturbs Ca 2ϩ homeostasis (25,41,42) and may act as a cross-linking agent (33). Hence, future studies should reveal whether a more specific and acute manipulation of ER ceramide levels influences SMSr oligomerization.…”
Section: Discussionmentioning
confidence: 99%